2008
DOI: 10.1111/j.1365-2966.2008.13272.x
|View full text |Cite
|
Sign up to set email alerts
|

Infrared contamination in Galactic X-ray novae

Abstract: The most widely used means of measuring the mass of black holes in Galactic binaries - specifically the X-ray novae - involves both radial velocity measurements of the secondary star, and photometric measurements of its ellipsoidal variability. The latter is important in constraining the inclination and mass ratio, and requires as direct a measure of the flux of the secondary as possible. Up to now, such measurements have been preferentially carried out in the near-infrared (NIR: 1-2.5 mu m), where the flux fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…Nevertheless, it has often been found that the accretion disc contributes 10–45 per cent to the optical R ‐band light in black hole transients (BHTs) in quiescence (see references above and e.g. Reynolds et al 2008 and references therein). Conservatively, assuming an accretion disc contribution of 50 per cent to the R ‐band luminosity and an M2 V companion star, we derive a distance of 5.9 kpc, which we round to 6 kpc.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it has often been found that the accretion disc contributes 10–45 per cent to the optical R ‐band light in black hole transients (BHTs) in quiescence (see references above and e.g. Reynolds et al 2008 and references therein). Conservatively, assuming an accretion disc contribution of 50 per cent to the R ‐band luminosity and an M2 V companion star, we derive a distance of 5.9 kpc, which we round to 6 kpc.…”
Section: Discussionmentioning
confidence: 99%
“…The extragalactic sources may also be contaminated by supernova remnants along the line of sight, though this can be mitigated by going to higher frequencies. Stellar mass uncertainties are dominated by uncertainties in distance, inclination, and light from accretion (see Reynolds et al 2008).…”
Section: 3mentioning
confidence: 99%
“…However, in no case has the disk contribution to the optical/NIR light curves been robustly constrained. In the most recent work, Gelino et al (2001) obtained an estimate of i = 54 • ± 1.5 • by modeling the J and K band light curves assuming that the disk contribution is negligible, an assumption that was subsequently shown to be ill-founded (Reynolds et al 2008;Kreidberg et al 2012). Based on the mass measurement of Gelino et al, Morningstar et al (2014) found a retrograde spin (a * = −0.25 +0.05 −0.64 ) for the black hole in NovaMus, which is a remarkable result for a black hole in a BHSXT, given that the spin of the black hole is believed to be accrued gradually over the lifetime of the system via accretion torques (Fragos & McClintock 2015).…”
mentioning
confidence: 99%